INCREASING THE EFFICIENCY OF INNOVATION ACTIVITY OF INDUSTRIAL ENTERPRISES IN THE DIGITAL ECONOMY (American Journal of Interdisciplinary Research and Development, 2023)
This article discusses the importance of introducing digital technologies in increasing the economic efficiency of industrial enterprises. The features of digitalization of industrial enterprises, in particular, the problems hindering the development of digitalization of industrial enterprises are studied and analyzed.